The electronic structure of silver orthophosphate: Experiment and theory - WATSON, GRAEME (My University, 2014)
Since the original discovery of the water-splitting activity of silver orthophosphate (Ag3PO4), considerable effort has been devoted to improving its photocatalytic activity and stability through morphology control and the design of multi-component electrode systems. Relatively little attention, however, has been paid to understanding the fundamental electronic properties of this material. Using X-ray photoelectron spectroscopy and hybrid density functional theory (DFT) calculations, we have studied the electronic structure of Ag3PO4. Our results indicate that hybrid DFT calculations closely reproduce the structural, electronic, and optical properties of Ag3PO4. From further analysis of the experimental and theoretical electronic structure data we have constructed a revised molecular orbital diagram for Ag3PO4 that highlights the strong covalent interactions formed in the tetrahedral PO4 structural units
PUBLISHED
Keywords: silver orthophosphate; silver orthophosphate